Severe Rhabdomyolysis without Systemic Involvement: A Rare Case of Idiopathic Eosinophilic Polymyositis. (1st July 2015) - Farooq, Ayesha; Choksi, Vivek; Chu, Andrew; Mankodi, Dhruti; Shaharyar, Sameer; O'Brien, Keith; Shankar, Uday
Abstract : Introduction . Eosinophilic polymyositis (EPM) is a rare cause of rhabdomyolysis characterized by eosinophilic infiltrates in the muscle. We describe the case of a young patient with eosinophilic polymyositis causing isolated severe rhabdomyolysis without systemic involvement. Case Presentation . A 22-year-old Haitian female with no past medical history presented with progressive generalized muscle aches without precipitating factors. Examination of the extremities revealed diffuse muscle tenderness. Laboratory findings demonstrated peripheral eosinophilia and high creatinine phosphokinase (CPK) and transaminase levels. Workup for the common causes of rhabdomyolysis were negative. Her CPK continued to rise to greater than 100, 000 units/L so a muscle biopsy was performed which showed widespread eosinophilic infiltrate consistent with eosinophilic polymyositis. She was started on high dose systemic corticosteroids with improvement of her symptoms, eosinophilia, and CPK level. Discussion . This case illustrates a systematic workup of rhabdomyolysis in the presence of peripheral eosinophilia. Many differential diagnoses must be considered before establishing a diagnosis of idiopathic eosinophilic polymyositis. To our knowledge, our case of eosinophilic polymyositis is unique as it presented with severe rhabdomyolysis without another organ involvement. Clinicians should maintain a high index of suspicion for this physically debilitating disease to aid in prompt diagnosis.